(untitled) (Journal of Parents and Teachers, 2014)
Society rejects the old. No one wants to grow old. But when a good day you stop reading the letter of the newspaper and your body begins to have small faults, you realize we all grow old. However, aging is not bad, but experience, maturity, serenity, deep understanding of life and attitude.